Legal Literacy and Cultural Awareness in the Inheritance System: An Islamic Law Study of Indigenous Muslim Communities in West Nusa Tenggara - Hasanah, Siti; Hayati, Mardiyah (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2025)
The variation in inheritance practices among indigenous Muslim communities in West Nusa Tenggara (NTB) Indonesia reflects a dynamic interaction between Islamic legal norms and local traditions. Although the Islamic inheritance law system (faraid) is widely recognised, its implementation is often adapted to customary values and family deliberation to preserve social harmony. This raises the question of how legal literacy and cultural awareness influence the choice of inheritance systems. This study analyses the dynamics of legal literacy and cultural awareness in the inheritance practices of the Sasak, Samawa, and Mbojo peoples. A qualitative approach with an exploratory case study design was employed to examine the interaction between Islamic legal principles and customary values. Data were obtained through in-depth interviews with customary leaders, religious figures, heirs, and village officials, supported by customary law documents, inheritance records, and academic literature. The data were analysed inductively using reduction, categorisation, and thematic interpretation based on the theories of legal pluralism, the objective of Islamic law (maqhasid al-syari'ah), and valid custom ('urf sahih). The findings reveal that varying levels of legal literacy shape contextual interpretations of Islamic inheritance law. The integration of maqhasid al-syari'ah and 'urf sahih preserves protection of wealth (hifz al-mal) and preservation of lineage(hifz al-nasl), demonstrating that Islamic law adapts to local socio-cultural contexts. The novelty of this research lies in mapping the interrelation between legal literacy, cultural awareness, and inheritance practices as a form of community-based on collective legal reasioning (ijtihad jama'i). Scientifically, this study strengthens Islamic legal pluralism, enriches the anthropological approach to Muslim family law, and recommends enhancing community-based legal literacy and contextual inheritance mediation.